#TITLE_ALTERNATIVE# - DESRINA MUNAF (NIM : 10105014); Pembimbing : Dr. Rieske Hadianti, ANISA
The presence of a number of diverse cellular-telephone operators in Indonesia and the products they offer, yields a problem in choosing the appropriate operator’s product in order to minimize monthly-cost. Consumers must also consider whether they have to use the Blackberry service or not. In this final assignment, a mathematical-model is presented where its solution can be used to see which operator’s product that provides minimum average monthly-cost based-on consumers way of communicating. By sensitivity-analysis on this mathematicalmodel, we obtain a product chart that gives mean estimation of minimized communication cost. This map shows us which product to be selected, including an advise whether to use Blackberry service or not.